2019
DOI: 10.15405/epsbs.2019.11.25
|View full text |Cite
|
Sign up to set email alerts
|

Identity And Multimodality Of Cultural Content In Elt Coursebooks For Yls

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The use of social semiotics in reading images has also been proposed by Kress and van Leeuwen (2006). The texts are analyzed to show the representation of cultural content through multimodal criteria based on Stec (2017) related to the core modes of image, language, sound, and music depicting cultural content in ELT course books and Cortazzi & Jin, (1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of social semiotics in reading images has also been proposed by Kress and van Leeuwen (2006). The texts are analyzed to show the representation of cultural content through multimodal criteria based on Stec (2017) related to the core modes of image, language, sound, and music depicting cultural content in ELT course books and Cortazzi & Jin, (1999).…”
Section: Methodsmentioning
confidence: 99%
“…Several published studies that have been conducted in the same field (Stec, 2017;Surmiyati & The, 2017;Pauwels, 2012) showed that multimodal analysis claimed to be a comprehensive approach when it comes to analyzing in vary core modes of image, language, sound, and music in different degree. In other words, these analyses would beneficial for teachers and educators to see their effectiveness for the learners as I believe that textbook Denatasa Permatasari Multimodal Analysis on The Cultural Content of Indonesian High School English E-Textbooks ENLIT Vol 2(2) ‖ 114 is a crucial matter for EFL learners.…”
Section: Denatasa Permatasarimentioning
confidence: 99%
“…Weninger's (2021) method of analyzing foreign-language textbooks was to study how multimodal content ''encodes and communicates ideas about the world.'' Thus, some critical studies sought to illuminate the ideological meaning of the multimodal native and target culture's elements or their roles in the context of a specific social culture (Joo et al, 2020;Setyono & Widodo, 2019;Stec, 2019). Although native cultural content is in the foreground of oversimplifying the composition in the cultural content, which does not offer practical suggestions for selecting and systematically arranging multimodal content in textbooks.…”
Section: A Perspective Of Multimodalitymentioning
confidence: 99%
“…The previous researchers also maintained that the indigenous cultural characters should play a critical role in language textbooks to provide cognitive and affective support. Studies on Poland's English textbooks discussed local and world cultural content and analyzed the positive effect of multimodal elements in different contexts (Stec, 2017(Stec, , 2019. These explorations were centered on the form, influence, and position of multimodal content that represented learners' native culture.…”
Section: A Perspective Of Multimodalitymentioning
confidence: 99%
“…Multimodality is constructed from a social semiotic theory emphasizing power, representation, and communication (Kress & van Leuween, 2001). The notion of modes is ascribed as a social and cultural resource to make meanings (Stec, 2019). For instance, modes are manifested in writing, images, gestures, and 3D objects.…”
Section: Introduction mentioning
confidence: 99%